Exploring the Path of Social Support During to Proactive Career Behavior through Resilience - Ni Made Dwi Ariani Mayasari; I Gede Riana; Ida Bagus Ketut Surya; Made Surya Putra (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2025)
This study investigates the role of social support as a predictor of students' proactive career behavior strengthened by resilience. This study focuses on dual-career students actively involved in the knowledge-based creative gig economy sector in Buleleng Regency, Indonesia. A total of 146 students were selected as respondents in the study using purposive sampling criteria, and the data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The result shows that social support has a positive and significant effect on proactive career behavior, with resilience as a mediator that strengthens this relationship. This finding provides new insights into the importance of social support for dual-career students in developing proactive behaviors to navigate career paths in the precarious world of the gig economy. This study underscores the importance of social support and resilience to strengthen student’s behavior in building networks and exploring career opportunities, primarily in the economy of the gig economy.